Effects of physical activity interventions on cognitive and academic performance in children and adolescents: a novel combination of a systematic review and recommendations from an expert panel. Issue 10 (30th July 2018) - Singh, Amika S; Saliasi, Emi; van den Berg, Vera; Uijtdewilligen, Léonie; de Groot, Renate H M; Jolles, Jelle; Andersen, Lars B; Bailey, Richard; Chang, Yu-Kai; Diamond, Adele; Ericsson, Ingegerd; Etnier, Jennifer L; et al.
Abstract : Objective: To summarise the current evidence on the effects of physical activity (PA) interventions on cognitive and academic performance in children, and formulate research priorities and recommendations. Design: Systematic review (following PRISMA guidelines) with a methodological quality assessment and an international expert panel. We based the evaluation of the consistency of the scientific evidence on the findings reported in studies rated as of high methodological quality. Data sources: PubMed, PsycINFO, Cochrane Central, Web of Science, ERIC, and SPORTDiscus. Eligibility criteria for selecting studies: PA-intervention studies in children with at least one cognitive or academic performance assessment. Results: Eleven (19%) of 58 included intervention studies received a high-quality rating for methodological quality: four assessed effects of PA interventions on cognitive performance, six assessed effects on academic performance, and one on both. All high-quality studies contrasted the effects of additional/adapted PA activities with regular curriculum activities. For cognitive performance 10 of 21 (48%) constructs analysed showed statistically significant beneficial intervention effects of PA, while for academic performance, 15 of 25 (60%) analyses found a significant beneficial effect of PA. Across all five studies assessing PA effects on mathematics, beneficial effects were reported in six out of seven (86%) outcomes. Experts put forward 46 research questions. The most pressing research priority cluster concerned the causality of the relationship between PA and cognitive/academic performance. The remaining clusters pertained to PA characteristics, moderators and mechanisms governing the 'PA–performance' relationship and miscellaneous topics. Conclusion: There is currently inconclusive evidence for the beneficial effects of PA interventions on cognitive and overall academic performance in children. We conclude that there is strong evidence for beneficial effects of PA on maths performance. The expert panel confirmed that more 'high-quality' research is warranted. By prioritising the most important research questions and formulating recommendations we aim to guide researchers in generating high-quality evidence. Our recommendations focus on adequate control groups and sample size, the use of valid and reliable measurement instruments for physical activity and cognitive performance, measurement of compliance and data analysis. PROSPERO registration number: CRD42017082505.